Ethnic persistence, assimilation and risk proclivity - Holger Bonin; Amelie F. Constant; Konstantinos Tatsiramos; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2006)
The paper investigates the role of social norms as a determinant of individual attitudes by analyzing risk proclivity reported by immigrants and natives in a unique representative German survey. We employ factor analysis to construct measures of immigrants' ethnic persistence and assimilation. The estimated effect of these measures on risk proclivity suggests that adaptation to the attitudes of the majority population closes the immigrant-native gap in risk proclivity, while stronger commitment to the home country preserves it. As risk attitudes are behaviorally relevant, and vary by ethnic origin, our results could also help explain differences in economic assimilation of immigrants.
urn:nbn:de:101:1-2008042932
Keywords: 330